2021
DOI: 10.1021/acsami.1c17341
|View full text |Cite
|
Sign up to set email alerts
|

Positive Role of Fluorine Impurity in Recovered LiNi0.6Co0.2Mn0.2O2 Cathode Materials

Abstract: Lithium-ion battery (LIB) recycling is considered as an important component to enable industry sustainability. A massive number of LIBs in portable electronics, electric vehicles, and grid storage will eventually end up as wastes, leading to serious economic and environmental problems. Hence, tremendous efforts have been made to improve the hydrometallurgical recycling process because it is the most promising option for handling end-of-life LIBs owing to its wide applicability, low cost, and high productivity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…[156][157][158][159] Note that, the peeled cathode materials from retired LIBs in an industrial process usually contain impurities, such as PVDF binders, carbon-based conductive agents, etc. [67,71,160] It is significant to realize the direct renovation of degraded cathode materials in such a complex system for the large-scale production. Intriguingly, Deng and co-workers found that, in a suitable molten salt medium, the spent cathode materials with acetylene black impurities could be directly regenerated, showing the comparable electrochemical performance to that of the fresh samples.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…[156][157][158][159] Note that, the peeled cathode materials from retired LIBs in an industrial process usually contain impurities, such as PVDF binders, carbon-based conductive agents, etc. [67,71,160] It is significant to realize the direct renovation of degraded cathode materials in such a complex system for the large-scale production. Intriguingly, Deng and co-workers found that, in a suitable molten salt medium, the spent cathode materials with acetylene black impurities could be directly regenerated, showing the comparable electrochemical performance to that of the fresh samples.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[64][65][66][67] Recently, several innovative direct regeneration strategies, such as solid-state, hydrothermal, eutectic, and electrochemical methods, have been proposed accordingly and applied to degraded cathode materials to restore their electrochemical performance without breaking down the microstructures, which exhibit gigantic potential in solving the forthcoming retired LIBs storm (Figure 4). [68][69][70][71] However, the current development of these direct regeneration techniques is still in infancy. Although the substantial researches have been carried out and published, [50,72] it is absent in the thorough summary and assessment of this kind of advanced route, which is much significant and pressing for the quick progress of direct regeneration technique and future practical application in industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the higher leaching rates and lower energy consumption, hydrometallurgy has been extensively adopted in industry. In general, the spent cathodes are first dissolved with acid with the addition of a reductive agent, followed by a complex separation process involving chemical precipitation or solvent extraction . Even if all metal ions can be leached out, the subsequent multistep separation usually leads to huge loss of metal ions, especially lithium, whose final recovery rate is even below 72% .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the spent cathodes are first dissolved with acid with the addition of a reductive agent, followed by a complex separation process involving chemical precipitation or solvent extraction. 10 Even if all metal ions can be leached out, the subsequent multistep separation usually leads to huge loss of metal ions, especially lithium, whose final recovery rate is even below 72%. 11 Furthermore, excessive employment of chemical reagents means serious flaws in terms of recycling costs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous work, insoluble carbon is determined to be a negative factor in hydrometallurgical recycling . Anion impurities such as fluorine (F – ) is found to be beneficial to the process, resulting in a degree of performance improvement for the recovered cathode compared to virgin . However, there is still further investigation needed to uncover the influence of other anion impurities in the hydrometallurgy process.…”
Section: Introductionmentioning
confidence: 99%